2016
DOI: 10.1111/cup.12738
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic features of multiple cutaneous squamous cell carcinomas of the lower extremity

Abstract: Recent studies suggest cutaneous squamous cell carcinomas (SCCs) of the leg, particularly those occurring multiply in sun exposed skin of nonimmunosuppressed women, are a distinct clinical subtype. There are few reports of the histopathologic features of this subtype. A retrospective chart review of 4 patients with multiple SCCs on the leg was performed and a total of 35 biopsies from the legs examined. Histopathologically, the tumors lacked adjacent actinic keratosis (AK) and often had adjacent basaloid retif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…In addition, the lack of defined pathologic criteria to distinguish between HLP and SCC represents a limitation. While our relatively small cohort limits broad generalizations, it corroborates the results of previous studies demonstrating good prognosis with multiple treatment modalities, including more conservative approaches, for SCCs in lower extremities in the general population 14 . Limitations of our study include its retrospective nature and small cohort due to the rarity of the HLP‐SCC phenomenon and limited availability of staging and size data.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, the lack of defined pathologic criteria to distinguish between HLP and SCC represents a limitation. While our relatively small cohort limits broad generalizations, it corroborates the results of previous studies demonstrating good prognosis with multiple treatment modalities, including more conservative approaches, for SCCs in lower extremities in the general population 14 . Limitations of our study include its retrospective nature and small cohort due to the rarity of the HLP‐SCC phenomenon and limited availability of staging and size data.…”
Section: Discussionsupporting
confidence: 79%
“…While our relatively small cohort limits broad generalizations, it corroborates the results of previous studies demonstrating good prognosis with multiple treatment modalities, including more conservative approaches, for SCCs in lower extremities in the general population. 14 Limitations of our study include its retrospective nature and small cohort due to the rarity of the HLP-SCC phenomenon and limited availability of staging and size data. Further prospective studies would be beneficial to improving our understanding and management of patients with concomitant diagnoses of HLP and SCC.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Solus et al 5 did an institutional review of 61 cSCC cases of the lower extremity and found that 69% of patients were female and 90% of the tumors were well-differentiated. Munday et al 6 recently did a retrospective chart review and analyzed the histopathology of SCC of the leg. They found most of the lesions were well-differentiated and keratoacanthoma like lesions were noted in approximately 40%.…”
Section: Discussionmentioning
confidence: 99%
“…4 "Eruptive squamous atypia" is another term that encompasses KASP as well as other cSCC mimics. [10][11][12] KASP usually lack a background of actinic keratosis 11,12 as well as the canonical DNAbinding domain TP53 mutations associated with 60%-90% of cSCC. [13][14][15][16] In contrast to KA, lesions called KASP and eruptive squamous atypia do not seem to self-regress; all three of these terms similarly describe atypical squamous histopathology that mimics SCC.…”
Section: Introductionmentioning
confidence: 99%